2018
DOI: 10.17219/acem/78020
|View full text |Cite
|
Sign up to set email alerts
|

The expression of selected molecular markers of immune tolerance in psoriatic patients

Abstract: Background. Psoriasis is a chronic autoinflammatory disease whose underlying molecular mechanisms remain unclear. The disease is mediated by the cells and molecules of both the innate and adaptive immune systems. Some T cell surface molecules, including neuropilin-1 (NRP1), programmed death 1 (PD-1) and the human leukocyte antigen G (HLA-G), are known to play a role in the maintenance of immune tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Thus, the lack of difference in sHLA-G concentration between psoriatic patients and healthy volunteers might suggest an insufficient mechanism which could limit immune responses and suppress pathologic immunity. Interestingly, in our previous study we did not find any difference in the mRNA HLA-G expression between the psoriatic patients and controls [20]. Both Aractingi et al [24] and Cardili et al [25] observed enhanced HLA-G expression within the psoriatic lesions, which may be suggestive of some modulating role of HLA-G+ T cells at the site of inflammation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, the lack of difference in sHLA-G concentration between psoriatic patients and healthy volunteers might suggest an insufficient mechanism which could limit immune responses and suppress pathologic immunity. Interestingly, in our previous study we did not find any difference in the mRNA HLA-G expression between the psoriatic patients and controls [20]. Both Aractingi et al [24] and Cardili et al [25] observed enhanced HLA-G expression within the psoriatic lesions, which may be suggestive of some modulating role of HLA-G+ T cells at the site of inflammation.…”
Section: Discussionmentioning
confidence: 70%
“…The soluble form of PD-1, however, acts as a decoy receptor able to bind and neutralize PD-1/PDL1 [4, 5]. In our recent studies we have found that both the expression of PDCD1 mRNA in peripheral blood mononuclear cells [20] and the expression of PD-1 protein on CD4+ and CD8+ T cells were significantly decreased in psoriatic patients both with and without arthritis [21]. Thus, the compromised PD-1 function on CD4 + and CD8+ T cells might indicate inappropriate activation status and suggest dysregulation of the immune suppression mechanisms, which may lead to abnormal, persistent T cell activation and cytokine production in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 119 studies met the selection criteria and were included. Of these, 19 studied clinical markers [ 18 36 ], 69 studied laboratory markers [ 27 , 37 , 38 , 40 55 , 57 73 , 75 – 96 , 124 133 ], and 32 studied genetic markers [ 97 113 , 115 123 , 134 139 ]. One study described both clinical and laboratory markers [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have examined the correlation between PD-1 expression and CPP [ 3 , 4 , 5 , 6 , 7 , 18 ]. PD-1, a cell surface membrane receptor expressed on various inflammatory cells, transduces inhibitory signals to immune cells, including effector T cells, and promotes Treg activity [ 3 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional regulatory T (Treg) cells disrupt immune tolerance, which leads to the induction of autoimmune and auto-inflammatory diseases, such as psoriasis [ 2 ]. In addition to the immune-suppressing cytokines released from Treg cells, some T cell surface molecules, including cytotoxic T lymphocyte-associated antigen 4 (CTLA4), neurophilin-1, human leukocyte antigen G, and the programmed cell death protein-1 (PD-1) that interacts with the programmed cell death ligand (PD-L1), play critical roles in immune tolerance [ 3 ]. Dysfunctional T cell surface molecules cannot inhibit the activity of inflammatory cells in patients with psoriasis.…”
Section: Introductionmentioning
confidence: 99%